Spatially resolved acoustic spectroscopy for rapid imaging of material microstructure and grain orientation - Smith, Richard J.; Li, Wenqi; Coulson, Jethro; Clark, Matt; Somekh, Michael G.; Sharples, Steve D. (IOP Publishing, 2014)
Measuring the grain structure of aerospace materials is very important to understand their mechanical properties and in-service performance. Spatially resolved acoustic spectroscopy is an acoustic technique utilizing surface acoustic waves to map the grain structure of a material. When combined with measurements in multiple acoustic propagation directions, the grain orientation can be obtained by fitting the velocity surface to a model. The new instrument presented here can take thousands of acoustic velocity measurements per second. The spatial and velocity resolution can be adjusted by simple modification to the system; this is discussed in detail by comparison of theoretical expectations with experimental data.